STRUKTUR DAN KOMPOSISI VEGETASI GULMA PADA TANAMAN JAGUNG (Zea mays L.) DI DESA SEDANG, KABUPATEN BADUNG, BALI - Ni Komang Nadya Maharani; Martin Joni; I Ketut Sundra (Program Studi Biologi Universitas Udayana, 2025)
Corn is the main food commodity that contains carbohydrates that the body needs and can improve the country's economy. In the production of corn, there are problems, namely the presence of weeds as pest organisms (OPT) which cause a decrease in quality and quantity. Based on this, the aim of this research is to determine the structure and composition of weeds associated with corn plants in Sedang Village, Badung Regency, Bali. The research was carried out using the quadratic method (Quadrat Sampling Technique) in the form of bush plots measuring 5m x 5m and herbaceous plots measuring 1m x 1m. Samples were taken at 4 planting time intervals and 5 repetitions. The ecological parameters used to analyze vegetation are the Importance Value Index (INP), Shannon-Wiener Species Diversity Index (H), Sorensen Similarity Index (IS), and Species Distribution Pattern. The research results showed that the composition of weed types consisted of 24 species and 11 families. The type that dominates the corn cultivation land in Medium Village is Cynodon dactylon weed (L.) Pers, with an INP value of 34.27% and Cyperus rotundus L. of 21.23%, where both types of weed are classified as vicious weeds that emit toxic allelopathic compounds. The Shannon-Wiener Species Diversity Index (H) is classified as a high weed, ranging from 0.70 to 3.74. The Similarity Index (IS) is in the low category, ranging from 19.23-26.79%. The distribution pattern of weed species ranges from 1.22 to 1.46, which indicates that it is clustered because the V/M value is > 1.